Early surgical intervention among patients with acute central cord syndrome is not associated with higher mortality and morbidity - Godzik, Jakub (J Spine Surg, 2019)
BACKGROUND: Conflicting reports exist regarding mortality and morbidity of early surgical decompression in the setting of acute central cord syndrome (ACS) in multisystem trauma despite evidence of improved neurological outcomes. Consequently, optimal decompression timing in ACS in multisystem trauma patients remains controversial. This study aims to determine the association between early surgery for acute traumatic central cord and all-cause mortality among multisystem trauma patients in the National Trauma Data Bank (NTDB) using propensity score matching. METHODS: We used the NTDB (years 2011–2014) to perform a retrospective cohort study, which included patients >18 years, with ACS (identified using ICD-9 coding). Collected patient data included demographics, surgery timing (≤24 hours, >24 hours), injury mechanism, Charlson comorbidity index (CCI), injury severity score (ISS), serious adverse events (SAE). Logistic regression and propensity matching were used to investigate the relationship between surgery timing and subsequent inpatient mortality. RESULTS: We identified 2,379 traumatic ACS patients. This group was 79.3% male with an average age of 56.3±15.2. They had an average ISS of 19.5±9.0 and mortality rate of 3.0% (n=72). A total of 731 (30.7%) patients underwent surgery for ACS within 24 hours. Univariate analysis did not show a significantly higher mortality rate in the early versus late surgery groups (3.8% vs. 2.7%, P=0.127). In unadjusted models, early surgery was not predictive of death or SAE + death in full (P=0.129, P=0.140) or matched samples (P=0.137, P=0.280). In models adjusted for age, ISS, and CCI, early surgery was predictive of death and SAE + death using the full sample (P=0.013, P=0.027), but not when using the propensity matched sample (P=0.107, P=0.255). CONCLUSIONS: Early surgical intervention does not appear to be associated with increased mortality among ACS patients unlike previously suggested. We theorize that survival noted within the NTDB is confounded by factors including existing comorbidities and multisystem trauma, rather than surgical timing. Delaying definitive surgical care may predispose patients to worsened greater neurological morbidity.